The Influence Of Narcissism and Tenure Of CEO On Indonesian Sharia Banking Performance - Ramdhani Kurniawati; Gustita Arnawati Putri; Made Wedaswari (International Journal of Management Research and Economics, 2024)
This researcher aims to explore how CEO narcissism affects banking performance in depth. This research aims to examine the relationship between CEO narcissism and CEO tenure on banking performance. Quantitative research methods were used in this research with purposive sampling which resulted in 64 samples from companies indexed on the Indonesia Stock Exchange from 2018 to 2021. This research was tested using the SPSS 21 application program. The results of this research provide evidence that CEO narcissism has a significant effect on performance. banking. CEO tenure does not have a significant effect on banking performance.